Reforma al código del trabajo en relación al trámite administrativo de visto bueno - Cabrera Macías, Ángel David (2023)
From the legal point of view, taking as a starting point the analysis of the approval as a legal figure whose objective is rooted in the necessary and essential balance of workeremployer relations. In this area, it has been known that despite the great legislative effort to provide Ecuadorian citizens with new laws and more expeditious procedures, their work is still unfinished because they maintain, so to speak, a pending subject in comprehensive legal reform for the causes of dismissal. justified and its corresponding procedure. Through this research project based on the different jurisprudential criteria of legislation based on international law and compared to the professional experience of our work context, it has been possible to demonstrate how ineffective and deficient the currently called approval is to find a solution. legal viable through a proposal that contemplates the change of the old denomination of approval for justified dismissal as well as reforms to the grounds for dismissal urgently arise, its procedure, limitation periods within the framework of our current legislation in Ecuador.